1978
DOI: 10.1071/ar9780789
|View full text |Cite
|
Sign up to set email alerts
|

The effect of defoliation on inflorescence production, seed yield and hard-seededness in swards of subterranean clover

Abstract: Swards of three strains of subterranean clover (Seaton Park, Yarloop, Midland B) were subjected to a range of defoliation treatments. In all strains, cutting at weekly intervals at a height of 1.5–2 cm from 1 month after sowing until the onset of flowering led to a slight delay in flower initiation but the time of flowering was little affected. The rate of inflorescence production, however, was always increased, as was the total number of inflorescences produced by the end of flowering. In particular, seed yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…An estimate of the average number of seeds set per plant showed that there was a tendency for all species to set more seeds per plant under high stocking rate than under low stocking rate (Table 1). A possible explanation could be that defoliation increased seed production probably because of increased branching, as reported, for example, in Trifolium subterraneum (Rossiter 1961(Rossiter , 1972Collins 1978).…”
Section: Effect Of Stocking Ratementioning
confidence: 90%
“…An estimate of the average number of seeds set per plant showed that there was a tendency for all species to set more seeds per plant under high stocking rate than under low stocking rate (Table 1). A possible explanation could be that defoliation increased seed production probably because of increased branching, as reported, for example, in Trifolium subterraneum (Rossiter 1961(Rossiter , 1972Collins 1978).…”
Section: Effect Of Stocking Ratementioning
confidence: 90%
“…Flowering time, physiological seed dormancy, and hardseededness are important plant factors (Donald 1960;Rossiter 1966;Collins et al 1976). However, their relative importance mayalterdepending on summerrainfall, grazing management, and plant competition (Quinlivan 1965;Ragon 1974;Collins 1978).…”
Section: Introductionmentioning
confidence: 98%
“…Defoliation once flowering has commenced is lower, with in vitro digestibility declining to 42-50% and crude known to reduce seed set with reductions becoming greater the protein (CP) to 9% (Mulholland et al 1996;Ru and Fortune later and more severe the defoliation (Collins 1978;Conlan 2001;Norman et al 2005). Rainfall over summer further et al 1994;Stockdale 2005).…”
Section: Introductionmentioning
confidence: 99%
“…defoliating before flowering commences on seed set is most The excess of herbage in spring is also a problem in pastures likely a result of increased branching of the runners and locked up for clover seed harvesting as the residues interfere promotion of burr burial (Rossiter 1961;Collins 1978; Collins with the recovery of the clover burr containing the seed. et al 1983).…”
Section: Introductionmentioning
confidence: 99%